MARKETING OF NITROGENATED FERTILIZERS IN MATO GROSSO - Caroline Ferreira Vidal, Érika; Zilocchi Miguel, Giulianna; Luiz Vieira, Carlos; Vinícius Batista da Silva, Gabriel; de Oliveira Figueiredo, Emerson (Journal of Interdisciplinary Debates, 2022)
Nitrogen fertilizers are generated from the manufacture of anhydrous ammonia (NH3), which involves the reaction of hydrogen with atmospheric nitrogen, and are used in energy sources such as natural gas, naphtha and asphalt waste. Among these hydrogen sources, natural gas is the most used and the most suitable, generating a greater concentration of nitrogen fertilizer producing units near petrochemical refineries. In Brazil, fertilizer production costs are considerably high due to logistical problems, represented by insufficient port infrastructure and freight prices, which increase the cost of imported raw material, consequently reflecting on the final price of fertilizers. Although the country shows high growth rates in the demand for fertilizers, the domestic production that provides its basic raw materials is not meeting its own demand. More than 80% of the fertilizers consumed in the country come from imports and domestic production accounts for less than 20% of the country’s demand. The state of Mato Grosso is the largest Brazilian agricultural hub with high rates of grain and fiber productivity, and areas available for growth. The researches carried out were descriptive, bibliographical and case study. Thus, the study aimed to analyze the behavior and price variation of nitrogen fertilizers, encompassing in a general way the national and world scenario with the state of Mato Grosso in recent years, and the difficulties encountered by the state and its future projections before the fertilizer market.